Pathology of Pigmented Skin Lesions - Plaza, Jose A.; Prieto, Victor G. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book offers a practical approach to the histologic analysis of a wide range of melanocytic skin lesions, including various nevi and different forms of melanoma, as well as pigmented non-melanocytic lesions. In addition, sentinel node biopsy findings and the use of special ancillary studies are covered in detail. Each chapter presents illustrative cases that document the route to correct diagnosis. An important feature of the book is the clinical-pathologic correlation of challenging melanocytic tumors; accordingly, it will appeal not only to pathologists (general surgical pathologists and dermatopathologists) but also to dermatologists (including dermatopathologists). The book contains some 250 color photos as well as tables and algorithms designed to assist in the diagnosis of difficult cases.